Soil Physical Properties and Water Utilization of Okra Under Irrigation and Mulching in Northern Guinea Savanna, Nigeria - Yusuf S. Alasinrin; Abdulkadir A. Wahab; Haliru A. Girei; Shamsiddeen M. Jibrin; Isiaka Karim; Olasunkanmi A. Odewole; Saheed S. Togun (Bulgarian Journal of Soil Science)
During the dry season, a field experiment was carried out at the IAR Irrigation Research Farm in Kadawa, Nigeria. The study investigated the impacts of controlled deficit irrigation and different mulch levels on soil hydro-physical traits and water efficacy in okra production (Abelmoschus esculentum L.). A total of Sixteen (16) treatment combinations were investigated: four irrigation levels (100, 85, 70, and 55% using weekly reference evapotranspiration (WRETo)) and four mulch levels (no mulch, 2, 4, and 6 kg/plot of rice straw). Soil samples at depths of 0-15 and 15-30 cm were analysed for bulk density (BD), total porosity (TP), saturated hydraulic conductivity (Ksat), and water retention across soil matrix potentials. Theta probes were used to measure soil moisture continually. The results showed that BD was statistically similar between 100% and 55% WRETo at 0-15 cm, but higher at 100% WRETo than at 85 and 70% WRETo. There were no significant variations in BD, TP, Ksat, or water potential across mulch layers or irrigation treatments at either depth. The RETC model effectively predicted soil hydraulic properties under the two treatments. Regarding yield, mulching at the M6 level boosted okra yield over other mulch treatments. The 55% ETo treatment achieved the highest irrigation water use efficiency (IWUE) at 20.99 kg/m³ compared to 100% ETo at 17.65 kg/m³. M6 and M4 mulch applications produced higher IWUE than M2 and M0 treatments, demonstrating that deficit irrigation and optimal mulching can improve water use efficiency in okra